2016
DOI: 10.1103/physrevapplied.5.064015
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide Metacouplers for In-Plane Polarimetry

Abstract: The state of polarization (SOP) is an inherent property of the vectorial nature of light and a crucial parameter in a wide range of remote sensing applications. Nevertheless, the SOP is rather cumbersome to probe experimentally, as conventional detectors only respond to the intensity of the light, hence loosing the phase information between orthogonal vector components. In this work, we propose a new type of polarimeter that is compact and well-suited for in-plane optical circuitry, while allowing for immediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 36 publications
(43 reference statements)
0
45
0
Order By: Relevance
“…It should be noted that the designed metasurfaces have a rather broadband response, featuring experimentally diffraction contrasts that closely represent Stokes parameters in the wavelength range of 750 − 850 nm. Following this concept, a waveguide metacoupler was proposed, which facilitates normal incident light to launch in-plane photonic-waveguide modes propagating in six predefined directions with the coupling efficiencies providing a direct measure of the incident SOP [308]. In the later work [304], an ultracompact in-line polarimeter has been demonstrated by using a 2D metasurface covered with a thin array of subwavelength metallic antennas embedded in a polymer film ( figure 16(e)).…”
Section: Polarimetersmentioning
confidence: 99%
“…It should be noted that the designed metasurfaces have a rather broadband response, featuring experimentally diffraction contrasts that closely represent Stokes parameters in the wavelength range of 750 − 850 nm. Following this concept, a waveguide metacoupler was proposed, which facilitates normal incident light to launch in-plane photonic-waveguide modes propagating in six predefined directions with the coupling efficiencies providing a direct measure of the incident SOP [308]. In the later work [304], an ultracompact in-line polarimeter has been demonstrated by using a 2D metasurface covered with a thin array of subwavelength metallic antennas embedded in a polymer film ( figure 16(e)).…”
Section: Polarimetersmentioning
confidence: 99%
“…Additionally, different types of metasurfaces were proposed to determine certain aspects of the SOP, like the degree of circular polarization. [28][29] Recently, on-chip metasurface-only polarimeters allowing for the simultaneous determination of all polarization states have been proposed and demonstrated, [30][31][32] but the implemented approaches are not suitable for extending to also conduct spectral analysis.…”
mentioning
confidence: 99%
“…[242][243][244][245][246][247][248] With a metasurface, vertical incidence light can couple into the waveguide, [249] and the waveguide can act as an in-plane polarimeter. [250] The effective relative permeability of the waveguide can also be controlled using split-ring resonators. [251] Recently, it was reported that phase gradient metasurfaces can be integrated into waveguides to realize mode conversion, polarization rotation and asymmetric optical power transmission.…”
Section: Discussionmentioning
confidence: 99%